PENGEMBANGAN INSTRUMEN UNJUK KERJA MATERI BANGUN RUANG DI SEKOLAH DASAR KOTA CIREBON - Rivo Panji Yudha (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2016)
The development of an authentic assessment instrument performance is a form of performance assessment instruments in elementary school mathematics learning that aims to measure the learning outcomes from the aspects of students' skills. This assessment instrument requires the use of a valid assessment of performance, realaiabel, practical, efficient and easy to learn. Research subjects in elementary school SDN Nurrusshidiq town of Cirebon and Cirebon City Karanganyar class V on the material geometry.Â This study is a model of the development of R & D using analysis of modified Borg and Gall researchers into three phases include: First, through the analysis of data needs that information obtained in the aspects of performance assessment instruments in learning mathematics are: preparation, execution and reporting of the work . Second, the lattice instrument consisting of 6 items, after tested retained as the 6th item is valid. Third, according to the input of the experts who were four people using the techniques of expert judgment, to-four experts came from three expert evaluation, and mathematical instruments and a senior Mathematics teacher. Fourth, the content validity of the test results were analyzed using the Q Score of all aspects assessed by experts covering aspects aspects Compliance with indicator, writing, language, and physical appearance ideals percentage value of 91% included in the criteria used very good and decent. Fifth, data from the instrument reliability performance on a small scale using GENOVA analysis, problem number one (0.89), Problem number two (0.90), question number three (0.82) about the number three (0.78). (4). Sixth, practicality uyang instruments were analyzed using T scores obtained an average score of 52.33 and a T score of each rater I (49), rater II (54), and a third rater score obtained from T (54) and based on the assessment teacher performance assessment instruments classified as practical .Â In conclusion authentic assessment instrument performance worthy to be used by primary school mathematics teacher and teacher summarized the results of all development in the use of manual performance assessment instrument. It is advisable for teachers to take advantage of the assessment instrument performance as a capability assessment of students in aspects of learning math skills in elementary school.